2008
DOI: 10.1007/s10549-007-9876-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations and genetic relations in benign, borderline and malignant phyllodes tumors of the breast: a comparative genomic hybridization study

Abstract: Phyllodes tumors are not quite rare fibroepithelial neoplasms of the breast that show a broad spectrum of clinical behaviour. The molecular genetic features of the heterogenous groups of neoplasms have not been studied in detail yet. We have used comparative genomic hybridization to analyze chromosomal copy number changes in 36 cases of phyllodes tumors (including benign, borderline and malignant phyllodes tumors, 12 cases each). The average number of chromosome copy changes (range) in benign, borderline and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
4
18
1
Order By: Relevance
“…This suggests that a classification of phyllodes tumors of the breast into two categories (benign and malignant) better reflects the genetic reality. Lv et al also confirmed that molecular CGH features of borderline and malignant PTs were similar [15]. They used CGH to identify chromosomal aberrations in 36 cases of benign, borderline, or malignant PTs of the breast.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This suggests that a classification of phyllodes tumors of the breast into two categories (benign and malignant) better reflects the genetic reality. Lv et al also confirmed that molecular CGH features of borderline and malignant PTs were similar [15]. They used CGH to identify chromosomal aberrations in 36 cases of benign, borderline, or malignant PTs of the breast.…”
Section: Discussionmentioning
confidence: 85%
“…Most recent studies of PTs have concentrated on the genetic changes detected in the tumors [13][14][15]. On the basis of patterns of chromosomal changes by comparative genomic hybridization (CGH), Laé et al classified PTs into two categories (benign and malignant) instead of three categories [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar chromosomal changes were identified by Jones et al 46 in their array-GCH analysis in 126 PTs. We must note, however, that Lv et al 47 found the gain of 1q did not correlate with grades, and Lu et al 48 reported that 1q gain was found mainly in benign PTs (6 of 12; 50%), underscoring the need for more conclusive investigations. Loss of 13q in PT suggests that the RB1 gene localized in these regions could be relevant to PT oncogenesis or progression.…”
Section: Molecular/genetic Featuresmentioning
confidence: 84%
“…2,10 There is also evidence that 1q gain and 4q12 gain may be associated with recurrent disease in malignant phyllodes tumors. 11 The diagnosis of phyllodes tumors and the assignment of a grading based on histologic characteristics are still associated with much uncertainty and variability.…”
Section: Discussionmentioning
confidence: 99%